2023
DOI: 10.1002/lary.30580
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen Genotyping of Idiopathic Subglottic Stenosis

Abstract: ObjectiveDespite recent scientific inquiry, idiopathic subglottic stenosis (iSGS) remains an enigmatic disease. The consistent demographics of the affected population suggest genetic factors may contribute to disease susceptibility. Given the inflammation observed in the affected proximal airway mucosa, we interrogated disease association with human leukocyte antigen (HLA) polymorphisms. Polymorphisms in the HLA locus have previously been shown to influence individuals' susceptibility to distinct inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The composition of an individual's TCR repertoire is the result of many forces, including age and HLA genotype. Previous work has shown that the HLA genotype of iSGS patients is similar to matched controls 47 . In addition to the role of HLA in driving overlap in TCR responses, data suggest increased age correlates with more shared low frequency TCR clones 48 .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The composition of an individual's TCR repertoire is the result of many forces, including age and HLA genotype. Previous work has shown that the HLA genotype of iSGS patients is similar to matched controls 47 . In addition to the role of HLA in driving overlap in TCR responses, data suggest increased age correlates with more shared low frequency TCR clones 48 .…”
Section: Discussionmentioning
confidence: 76%
“…Previous work has shown that the HLA genotype of iSGS patients is similar to matched controls. 47 In addition to the role of HLA in driving overlap in TCR responses, data suggest increased age correlates with more shared low frequency TCR clones. 48 The average age of our iSGS cohort meets immunologic definitions of "increased age" (>40 years) at 54 (+/À 8 years), and yet there was minimal overlap in TCR clones observed.…”
Section: Discussionmentioning
confidence: 99%
“…A potential association between a specific upper airway microbiota, especially members of the Moraxellaceae family, and ISGS has also been discussed (6). In contrast to patients with granulomatosis with polyangiitis a human leucocyte antigen (HLA) association with allele DPB1*04:01 or allele homozygosity was excluded in ISGS (7). Among ISGS patients, clonality of the TCR repertoire is driven by CD8+ T cells, and ISGS patients possess numerous TCRs targeting viral and intercellular pathogens.…”
Section: Introductionmentioning
confidence: 99%